Dancing Bees - Ranjit Lal (Chennai,India Tulika Publications, 2005)
Did You Know That Bees Make A Real Song And Dance Over Honey? And Delicate Butterflies Can Frighten Fearsome Birds? Superbly Comic Pictures Exaggerate Funny But True Facts About The Mad, Mad World Of Creepy Crawlies.
Keywords: Read Aloud -- Read Aloud